Phytotoxic effects of Aeschynomene fluminensis Vell. on the initial growth of weeds and cultivated plants (Research, Society and Development, 2021)
Allelopathy is analyzed as an alternative to herbicides due to the inhibitory or beneficent activities of its compounds with other organisms. Current paper discusses the effects of Aeschynomene fluminensis Vell. fractions on cultivated plant species, Lactuca sativa L. and Glycine max (L.) Merril, and on weeds, Ipomoea grandifolia (Dammer) O’Donnel and Digitaria insularis (L.) Fedde. Aqueous fractions at 0.80; 0.40; 0.20 and 0.10 mg mL-1 concentrations were employed for initial growth tests. Seeds were pre-germinated in distilled water and transferred to petri plates with separate fractions at different concentrations. Plates were maintained for 48 h in a germination chamber at 25°C for L. sativa and I. grandifolia and at 30°C for G.max and D. insularis. The length of hypocotyl (LH) and root (LR) was measured and LR and foliar length (LF) were taken for D. insularis seedlings. Parameters were employed to calculated inhibition percentage. Plants with morphological changes were fixed and analyzed anatomically. Results revealed LH and LR inhibition of lettuce seedlings in fractions with highest concentration rates. The same has been reported in the case of I. grandifolia. Butanolic, methanolic and chloroform fractions did not affect negatively soybean seedlings but they inhibited D. insularis seedlings´ LR. A. fluminensis fractions, especially at higher concentrations, inhibited seedlings´ growth and confirmed their phytotoxic capacity.